2010
DOI: 10.3892/ol_00000019
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of neutrophil gelatinase-associated lipocalin and its receptor in colorectal carcinoma: Significant correlation with cell differentiation and tumour invasion

Abstract: Abstract. neutrophil gelatinase-associated lipocalin (ngAl), a member of the lipocalin family, is related to imflammation and tumour. Recently, a specific cell-surface receptor (24p3R/ NGALR) for lipocalin 24p3 was reported. However, the characteristics of ngAlr expression in colorectal carcinoma (crc) are not known. The objectives of this study were to investigate the expression of ngAl and ngAlr in crc specimens, and determine any relationship between the expression of these proteins and tumour progression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Studies have been carried out to compare the NGAL expression levels in CRC with other tumor features such as cancer differentiation and localization of the tumor. As a result of these studies there were no significant correlations between NGAL expression level and tumor localization or cancer differentiation (25,39). Likewise, we did not find a correlation between serum NGAL levels and these features.…”
Section: Discussion Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Studies have been carried out to compare the NGAL expression levels in CRC with other tumor features such as cancer differentiation and localization of the tumor. As a result of these studies there were no significant correlations between NGAL expression level and tumor localization or cancer differentiation (25,39). Likewise, we did not find a correlation between serum NGAL levels and these features.…”
Section: Discussion Discussioncontrasting
confidence: 51%
“…Nevertheless, there are inconsistent and even contradictory reports on the role of NGAL in the development and progression of cancer. Various studies were presented in the literature about genetic and immunohistochemical analyses on tissue samples to evaluate the diagnostic value of NGAL in CRC (19,21,25,(38)(39)(40). However, there is only one study available in current literature to evaluate the relationship between serum NGAL level and CRC.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…The present study is the first to have shown that the receptor for NGAL (SLC22A17; absent or weakly expressed in normal PBMCs) is strongly expressed by tumoral B cells from untreated CLL patients. Both NGAL and NGAL-R are upregulated in CLL, a situation similar to their expression pattern in various solid tumors where they are associated with clinical prognosis [56][57][58][59][60]. After treatment, total and surface NGAL-R levels fell to baseline levels in patients achieving clinical remission.…”
Section: Discussionmentioning
confidence: 79%
“…Lv et al investigated expression of NGAL using R&D Systems antibodies (Minneapolis, MN, USA) in specimens of 102 patients with colorectal cancer [44]. Expression of NGAL was significantly higher in colorectal cancer specimens compared with adjacent normal tissues (28.4% vs. 0%; p < 0.001).…”
Section: Colorectal Cancersmentioning
confidence: 99%
“…Synopsis of available epidemiological studies linking neutrophil gelatinase-associated lipocalin (NGAL) with different forms of cancer Serum NGAL did not differ between cancer patients and controls ○ Urine NGAL 3.6-fold higher in cancer patients than in controls NGAL expression in 69% of cases ○ Higher NGAL expression in cancerous than in adjacent normal tissue ○ NGAL expression associated with depth of invasion, lymph node metastasis, venous involvement, and advanced stage Serum NGAL higher in high-risk patients, in those with >3 cancer nodules and with both lobes involvement Lv et al[44] Colorectal cancer Immunohistochemistry 102 -○ Higher NGAL expression in cancerous than in adjacent normal tissue ○ NGAL expression associated with cancer invasion…”
mentioning
confidence: 96%